2019
DOI: 10.1126/sciadv.aay0001
|View full text |Cite
|
Sign up to set email alerts
|

Disengagement of motor cortex from movement control during long-term learning

Abstract: Motor learning involves reorganization of the primary motor cortex (M1). However, it remains unclear how the involvement of M1 in movement control changes during long-term learning. To address this, we trained mice in a forelimb-based motor task over months and performed optogenetic inactivation and two-photon calcium imaging in M1 during the long-term training. We found that M1 inactivation impaired the forelimb movements in the early and middle stages, but not in the late stage, indicating that the movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 40 publications
(59 reference statements)
18
76
0
Order By: Relevance
“…Second, because motor cortex plays less of a role in driving striatum as behaviors become highly practiced, lesioning, inactivating, or randomly perturbing activity in motor cortex during behavior should have a decreasingly small effect on the behavior the more that it has been trained (Figure 7b). This effect has in fact already been observed in very recent experiments using optogenetic inactivation throughout learning of a targeted forelimb task [48].…”
Section: Input Alignment and Control Transfer In The Two-pathway Modelsupporting
confidence: 53%
See 1 more Smart Citation
“…Second, because motor cortex plays less of a role in driving striatum as behaviors become highly practiced, lesioning, inactivating, or randomly perturbing activity in motor cortex during behavior should have a decreasingly small effect on the behavior the more that it has been trained (Figure 7b). This effect has in fact already been observed in very recent experiments using optogenetic inactivation throughout learning of a targeted forelimb task [48].…”
Section: Input Alignment and Control Transfer In The Two-pathway Modelsupporting
confidence: 53%
“…As described in the previous section, the transfer of control from corticostriatal to thalamostriatal inputs would suggest that motor cortex should be necessary for the initial learning of a behavior, but not for the production of the behavior after a sufficient amount of practice. Evidence for this has recently been found in studies using lesions [47] or inactivations [48] to test the involvement of motor cortex in rodents performing skilled forelimb tasks. In addition, studies of learned motor behaviors in humans have suggested that motor cortex becomes less involved in driving behaviors with practice [49,50], consistent with the proposed sensorimotor implementation of the two-pathway model.…”
Section: Input Alignment and Control Transfer In The Two-pathway Modelmentioning
confidence: 91%
“…For instance, skill learning, disease or trauma can induce experiencedependent changes in motor cortical representations, including expansions of motor maps that may reflect functional reorganization to support newly learned movements (Sanes and Donoghue, 2000;Li et al, 2001;Conner et al, 2005;Xu et al, 2009;Makino et al, 2016;Peters et al, 2017;Papale and Hooks, 2018). Moreover, while the necessity of motor cortex for performance of learned skills can vary depending on factors such as the level of dexterity required or the amount of time spent training, motor cortex is required for the acquisition of new motor skills across a variety of movements and training paradigms (Whishaw et al, 1991;Whishaw, 2000;Darling et al, 2011;Guo et al, 2015;Kawai et al, 2015;Hwang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of motor control, our findings also encourage to study the role of areas found to be active during movement (such as the visual areas) commonly disregarded in the association to forelimb movement, at the cellular-level (Galiñanes et al, 2018, Karandell and Huber, 2017, Ebina et al, 2018). In the future, it would also be relevant to assess the neocortical dynamics during RtG in a freely moving condition or during performance refinement, considering that cortical areas undergo functional reorganization during learning (Makino et al, 2017; Whishaw et al, 2017; Bollu et al, 2019; Hwang et al, 2019). In sum, our investigation identified a global network of neocortical area associated to successful RtG execution.…”
Section: Discussionmentioning
confidence: 99%